2015
DOI: 10.1021/acsnano.5b05055
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation of G:C vs A:T and G:C vs G:mC Base Pairs in the Latch Zone of α-Hemolysin

Abstract: The alpha-hemolysin (α-HL) nanopore can detect DNA strands under an electrophoretic force via many regions of the channel. Our laboratories previously demonstrated that trapping duplex DNA in the vestibule of wild-type α-HL under force could distinguish the presence of an abasic site compared to a G:C base pair positioned in the latch zone at the top of the vestibule. Herein, a series of duplexes were probed in the latch zone to establish if this region can detect more subtle features of base pairs beyond the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…The observed ~0.5 pA current difference between the nicked and repaired duplexes is likely due to one additional negative charge, the PO 4 2− on the 5’ end of the 8-mer probe, which we speculate may increase the local counter-ion concentration at the latch zone in addition to modulating the ion flux blockade via duplex structure modification, as previously reported for single base recognition. 13, 21, 51 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed ~0.5 pA current difference between the nicked and repaired duplexes is likely due to one additional negative charge, the PO 4 2− on the 5’ end of the 8-mer probe, which we speculate may increase the local counter-ion concentration at the latch zone in addition to modulating the ion flux blockade via duplex structure modification, as previously reported for single base recognition. 13, 21, 51 …”
Section: Resultsmentioning
confidence: 99%
“…20 Further investigation of the latch constriction of α-HL has demonstrated that one G:C base pair can be distinguished from an A:T pair, as well as single-base mismatches (e.g., C:C or C:A), based on current blockade levels. 2122 Recently, we also observed that mismatched base pairs induce characteristic ion current modulations in the α-HL channel. 2223 …”
Section: Introductionmentioning
confidence: 95%
“…136, 137 Detection of both single base-pair replacement (e.g., GC pair replaced by AT pair) and epigenetic markers (e.g., 5-methylcytosine) has also been achieved with α-HL latch sensors. 139 …”
Section: Biological Nanoporesmentioning
confidence: 99%
“…These ion channel recordings can be used to identify changes to DNA structure such as damage, 3739 methylation 40 and mismatch 36 sites. In a typical experiment, a DNA helix, modified with a threading poly-T tail at the end of one strand, is driven into the αHL nanopore (embedded in a lipid bilayer) under an applied potential (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…37, 38, 40 A DNA duplex containing a single mismatched base-pair positioned at the latch constriction results in a current signature that modulates between two distinct states ( I 1 and I 2 ). In contrast, for a fully-complementary reference duplex, no modulation is observed (Figure 1B).…”
Section: Introductionmentioning
confidence: 99%